Effect Of Metacognitive Strategy Instruction On Cefr b1 English Level Learner´s Reading Comprehension Skill In An Ecuadorian Efl Class - Espol (2017)
The ability to read and understand information is vital in a world where data is reached at one single click. Saricoban (2012) claims that reading is the most stressed skill in english as a foreign language (efl) classes. In ecuador, the new regulation of the government demands university students to get a b1 level before reaching the 60% of the total number of credits to continue with their majors (reglamento de régimen académico, 2015). The current study pretended to shed some light on the importance of teaching metacognitive reading strategies to students so that it becomes an independent process rather than aproduct to measure by questions. the study took place in a private university of cañar. There were 40 participants in total at a b1 level. The researchers applied a placement test to confirm the level of students. Also, the researchers used a pre and a post-test. Both tests were the same. matched t-test statistics were used to analyze